The effect of iron supplementation in preterm infants at different gestational ages - Sufeng Ruan; Jinrong Li; Fei Xiong; Di Qie; You Lu; Sufei Yang; Zhanghui Tang; Fan Yang (BMC, 2024)
Abstract Background Iron deficiency (ID) is the most prevalent nutritional deficiency disease in preterm infants, significantly affecting their growth and development. For preterm infants to flourish physically and neurologically, timely iron supplementation is essential. The main goals of this study were to determine whether the present iron supplementation regimen results in iron overload in late preterm infants and whether it can meet the growth requirements of early preterm infants for catch-up. Methods We conducted a prospective follow-up study on preterm infants at the Department of Child Health, West China Second University Hospital, Sichuan University, from January 1, 2020, to August 31, 2020. In this study, 177 preterm infants were divided into two groups based on gestational age-early preterm infants (gestational age < 34 weeks) and late preterm infants (gestational age ≥ 34 weeks and < 37 weeks)-to compare the incidence of iron deficiency, iron status, and physical growth of preterm infants receiving iron supplements (2-4 mg/kg/d). Results Iron supplementation considerably reduced the incidence of iron deficiency in preterm infants. The prevalence of iron deficiency in early preterm infants and late preterm infants was 11.3% and 5.1%, respectively, at the corrected gestational age of 3 months; at the corrected gestational age of 6 months, the prevalence was 5.3% and 6.3%, respectively. No preterm infants with iron deficiency were detected in either group at the corrected gestational age of 12 months. Ferritin was substantially lower in early preterm infants (36.87 ± 31.57 ng/ml) than in late preterm infants (65.78 ± 75.76 ng/ml) at the corrected gestational age of 3 months (p < 0.05). A multifactorial regression analysis of factors influencing iron metabolism levels in preterm infants revealed a positive relationship between log10hepcidin, birth weight, and ferritin, with higher birth weights resulting in higher ferritin levels. Conclusions Postnatal iron supplementation at 2-4 mg/kg/d in preterm infants significantly decreases the incidence of ID. There were substantial differences in iron levels across preterm infants of varying gestational ages. A tailored iron supplementation plan based on growth, birth weight, and gestational age may be a more suitable route for iron supplementation. Although the current study found that the postnatal iron status of early preterm infants differed from that of late preterm infants, the actual mechanism of action remains unknown, and large-sample, multicenter clinical studies are required to investigate this further.